Music therapy approach in chemical dependence based on the Transtheoretical Model of Change - Frederico Gonçalves Pedrosa; Frederico Duarte Garcia; Cybelle Maria Veiga Loureiro (Per Musi, 2022)
The Transtheoretical Model of Change (TMC) was created by Prochaska and DiClemente in (1982), and has supported clinical work on Chemical Dependence since its origins from Stages of Change. This text presents a rationale for music therapy treatment in chemical dependency supported by the Rational Scientific Model of Mediation in interfaces with the TMC. Thus, we discuss the neurophysiological bases of music processing as well as drugs abuse, we point out as already proven effective music therapy techniques for music therapy treatment with such a population, we present the TMC and, finally, we point out which techniques are more efficient for the different phases of treatment. This research will support the creation of an assessment instrument that informs whether the music therapy process helps in the evolution of chemically dependent patients.